1987
DOI: 10.1111/j.1751-1097.1987.tb04838.x
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH DELAY STUDIES OF THE RESPONSE OF V‐79 MULTICELL SPHEROIDS EXPOSED TO DHE and RED LIGHT

Abstract: Multicell tumour spheroids (MTS) of V‐79 Chinese hamster cells have been used to study the role of a number of treatment and microenvironmental parameters in the modification of tumour response to Photodynamic Therapy (PDT) using visible light in combination with the photosensitizing compound dihematoporphyrin ether (DHE). The kinetics of DHE uptake into MTS, determined by fluorimetry of extracted porphyrins, indicate that after extended incubation (i.e. 24 h) the mean cellular DHE content in larger (˜300 μ.m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Subsequent growth delay was observed for both PDT doses (figure 10(a)), with an initial transient swelling in the high-dose group. Similar responses have been described by Jeeves et al (1987). Light and electron microscopy revealed that the depth of damage below the surface increased with light dose (figure 9).…”
Section: Spheroid Responses In Vitrosupporting
confidence: 84%
See 1 more Smart Citation
“…Subsequent growth delay was observed for both PDT doses (figure 10(a)), with an initial transient swelling in the high-dose group. Similar responses have been described by Jeeves et al (1987). Light and electron microscopy revealed that the depth of damage below the surface increased with light dose (figure 9).…”
Section: Spheroid Responses In Vitrosupporting
confidence: 84%
“…Spheroids thus represent a 3D tumour model to investigate purely cellular changes without extraneous in vivo factors. Spheroids have been used to study PDT response (Jeeves et al 1987, West 1988) and the effects of the microenvironment (O 2 , pH) on this (Chan et al 1991) and to quantify the effects of photobleaching and photochemical depletion of oxygen during PDT (Mitra and Foster 2000). The goal here was to determine whether EIS is sensitive to purely cellular PDT damage and whether it can discriminate between necrosis and apoptosis, both of which are believed to occur with PDT, depending on the exact treatment conditions (Oleinick and Evans 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This, and other early studies, focused mainly on evaluating hematoporphyrin (Hpd) distributions and the effects of Hpd-PDT in a variety of MCS models [15][16][17][18][19]. In particular, fundamental studies by West [16] and West et al [19] demonstrated that human colon carcinoma spheroids were more resistant to Hpd-PDT compared to monolayers and that the sensitivity to PDT decreased with increasing spheroid size.…”
Section: Mcs In Basic Pdt Studiesmentioning
confidence: 99%
“…Three-dimensional multicellular spheroids, tumour models intermediate between cell monolayers and organized tumours, are typically more resistant to PDT than exponentially growing monolayers (Christensen et al 1984, Jeeves et al 1985 and this resistance is spheroid size dependent (West 1989). A decrease in photosensitizer uptake with increasing spheroid size has been demonstrated (Jeeves et al 1987, West 1989, West and Moore 1992) and an increase in heterogeneity of intracellular drug levels with increasing spheroid size (leading to the loss of the shoulder of the survival curve) for large spheroids (West and Moore 1989b). Cellular sub-populations resistant to PDT, that have been sorted from spheroids, have been shown to have smaller median cell volumes, to be enhanced in G 1 -type cells and to show reduced LDL uptake (West and Moore 1992).…”
Section: Cell Death and 'Survival' After Pdtmentioning
confidence: 99%